2015
DOI: 10.1186/s13071-015-0872-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cyclospora in captive chimpanzees and macaques by a quantitative PCR-based mutation scanning approach

Abstract: BackgroundCyclospora is a protistan parasite that causes enteritis in several species of animals including humans. The aim of this study was to investigate the presence of Cyclospora in captive non-human primates.MethodsA total of 119 faecal samples from Pan troglodytes, Macaca sylvanus, Cercopithecus cephus, Erythrocebus patas, Chlorocebus aethiops and Macaca fascicularis from a wildlife animal rescue center as well as from Macaca fascicularis from an experimental primate research center were tested for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 35 publications
0
25
0
3
Order By: Relevance
“…have been reported to be critical for veterinary health because it has been isolated from both domestic and street dogs, chicken in ecozonal region near forest areas, and rhesus monkeys (Macaca mulatta) wandering via the forest region (25), red panda in community forest (8) and goats brought for meat purposes from different areas (9), one or more of hosts like mice, rats, dogs, and chicken (2,26,27) although Cyclospora in domestic animals and birds were not detected previously (2,28). In addition to this Himalayan country, this coccidian has been reported in cattle from China (5), calf from Japan (29), monkeys from China (7,30), Ethiopia (31), and captive primates from Europe (32) although no reports on the stool of various cattle, birds, and wild animals from Haiti (33). Thus, though risks of this coccidian have been implicated in food-borne, soil-borne, water-borne, and fecal-borne transmissions (34)(35)(36), in the absence of detailed epidemiologic and molecular evidence, it is not easy to link this coccidian with zoonosis in goral.…”
Section: Discussionmentioning
confidence: 99%
“…have been reported to be critical for veterinary health because it has been isolated from both domestic and street dogs, chicken in ecozonal region near forest areas, and rhesus monkeys (Macaca mulatta) wandering via the forest region (25), red panda in community forest (8) and goats brought for meat purposes from different areas (9), one or more of hosts like mice, rats, dogs, and chicken (2,26,27) although Cyclospora in domestic animals and birds were not detected previously (2,28). In addition to this Himalayan country, this coccidian has been reported in cattle from China (5), calf from Japan (29), monkeys from China (7,30), Ethiopia (31), and captive primates from Europe (32) although no reports on the stool of various cattle, birds, and wild animals from Haiti (33). Thus, though risks of this coccidian have been implicated in food-borne, soil-borne, water-borne, and fecal-borne transmissions (34)(35)(36), in the absence of detailed epidemiologic and molecular evidence, it is not easy to link this coccidian with zoonosis in goral.…”
Section: Discussionmentioning
confidence: 99%
“…, pero más elevada que las observadas en otras partes de Venezuela, incluyendo otras poblaciones del semiárido falconiano 23,37,38,[40][41][42][43] . La ciclosporiosis es una enterococcidiosis muy común en las regiones tropicales y subtropicales del mundo, se le considera una infección emergente tanto en individuos inmunocompetentes como inmunosuprimidos, siendo la diarrea acuosa el síntoma más común, la cual resulta más severa en los inmunocomprometidos en especial los de VIH/SIDA, y en niños y ancianos; también se pueden presentar malabsorción con pérdida de peso, dolor abdominal, náusea, anorexia, flatulencia, fatiga y fiebre moderada, e inclusive existen reportes de casos fatales; a C. cayetanensis se le considera uno de los agentes causales de la denominada "diarrea del viajero" en individuos foráneos mientras visitan las zonas endémicas, por lo que en una región como la falconiana y especialmente la Península de Paraguaná, donde la afluencia de turistas es muy fluida durante la épocas de festejos y/o vacacionales, es de suma importancia el estudio de la situación epidemiológica de esta enteroccidiosis, la cual pudiera tener un componente zoonótico 1,3,25,[44][45][46][47][48] .…”
Section: Discussionunclassified
“…Conociéndose el comportamiento zoonótico de Cryptosporidium spp. y posiblemente de C. cayetanensis 1,3,[44][45][46][47][48] , los habitantes de esta población del semiárido falconiano corren el riesgo potencial de contaminación fecal de estas parasitosis a través de los animales domésticos y silvestres, por lo que se requiere estudiar la presencia de los entero-coccidios en los mismos. En este sentido se debe indicar que C. ubiquitum se aisló recientemente en seres humanos en Venezuela 58 ; esto se resalta debido a que esta especie de Cryptosporidum spp.…”
Section: Discussionunclassified
“…Cyclospora spp. were detected in non-host primates in the wild and in captivity (Li et al, 2015b;Marangi et al, 2015) and in shellfish (Aksoy et al, 2014). However, the majority of infections have been detected within the primary host species.…”
Section: Host Specificitymentioning
confidence: 99%
“…Studies have not yet identified domestic or wild animals as the source of infection in humans, although contact with animals has been associated with infection (Marangi et al, 2015). C. cayetanensis has been found in shellfish (Aksoy et al, 2014).…”
Section: Wildlifementioning
confidence: 99%